Predictive Value of C-Reactive Protein (CRP) in Identifying Fatal Outcome and Deep Infections in Staphylococcus aureus Bacteremia - Molkanen T; Ruotsalainen E; Rintala EM; Jarvinen A (PUBLIC LIBRARY SCIENCE, 2022)
IntroductionClear cut-off levels could aid clinicians in identifying patients with a risk of fatal outcomes or complications such as deep infection foci in Staphylococcus aureus bacteremia (SAB). Cutoff levels for widely used clinical follow-up parameters including serum C-reactive protein (CRP) levels and white blood cell counts (WBC) have not been previously studied.Methods430 adult SAB patients in Finland took part in prospective multicentre study in which their CRP levels and WBC counts were measured on the day of the positive blood culture, every other day during the first week, twice a week during hospitalization and at 30 days. Receiver operating characteristic (ROC) analysis was used to evaluate the prognostic value of CRP and WBC on the day of the positive blood culture and at days 4, 7, and 14 in predicting mortality and the presence of deep infections at 30 days. Adjusted hazard ratios (HR) for CRP level and WBC count cut-off values for mortality were calculated by the Cox regression analysis and adjusted odds ratios (OR) for cut-off values to predict the presence of deep infection by the binary logistic regression analysis.ResultsThe succumbing patients could be distinguished from the survivors, starting on day 4 after the positive blood culture, by higher CRP levels. Cut-off values of CRP for day 30 mortality in adjusted analysis, that significantly predicted fatal outcome were at day 4 CRP > 103 mg/L with sensitivity of 77%, specificity of 55%, and HR of 3.5 (95% CI, 1.2-10.3; p = 0.024), at day 14 CRP > 61 mg/L with a sensitivity of 82%, specificity of 80% and HR of 3.6 (95% CI, 1.1-10.3; p<0.039) and cut-off value of WBC at day 14 > 8.6 x 10(9)/L was prognostic with sensitivity of 77%, specificity of 78% and HR of 8.2 (95% CI, 2.9-23.1; p<0.0001). Cut-off values for deep infection in adjusted analysis were on the day of the positive blood culture CRP > 108 mg/L with sensitivity of 77%, specificity of 60%, and HR of 2.6 (95% CI, 1.3-4.9; p = 0.005) and at day 14 CRP > 22 mg/L with sensitivity of 59%, specificity of 68%, and HR of 3.9 (95% CI, 1.6-9.5; p = 0.003). The lack of decline of CRP in 14 days or during the second week were neither prognostic nor markers of deep infection focus.ConclusionsCRP levels have potential for the early identification of SAB patients with a greater risk for death and deep infections.